Potential of silica from water treatment sludge modified with chitosan for Pb(II) and color adsorption in sasirangan waste solution - Wicakso, Doni Rahmat; Mirwan, Agus; Agustin, Era; Nopembriani, Nova Fitria; Firdaus, Ikhsan; Fadillah, Muhammad (Communications in Science and Technology, 2022)
Water treatment sludge (WTS) still contains a lot of silica oxide (SiO2) as much as 43.12-66.90% by weight and can act as an adsorbent to be applied to the treatment of Sasirangan wastewater. Silica extraction from WTS was carried out by microwave-assisted leaching, which - compared to conventional extraction - had several advantages including high extraction yields, fast, uniform, and more selective processing time. In addition, Sasirangan liquid waste is a by-product of the dyeing process of Sasirangan cloth, which still contains heavy metals in amounts exceeding the quality standard. This study aims to extract silica from WTS by microwave-assisted leaching process to synthesize silica modified by chitosan (Si-Kit) as an adsorbent to reduce Pb(II) from Sasirangan wastewater, and to obtain a kinetic model of the adsorption process. The silica from microwave-assisted leaching process (Si-MaL) and Si-Kit adsorbents were characterized using FTIR and SEM. The results showed that the dominant functional groups of Si-Kit included Si-O-Si, Si-O-C stretching vibrations, and stretching vibration of C=N showing that the condensation between aldehyde groups and amino groups occurred to form base after the addition of glutaraldehyde. The SEM images showed that Si-MaL and Si-Kit adsorbent obviously increased in particle size with the presence of visible particles of homogeneous granules and large pores. The removal efficiency percentage of Pb(II) and color occurred at 6% w/v adsorbent weight and 70 min was 87.20% and 61.87% respectively. Meanwhile, the adsorption kinetics of Pb(II) and color followed the zero order kinetics model at weight variation of 6%-w/v based on the value of R2 close to one and the adsorption capacity of Pb(II) ion and color were 12.01 mg g-1 and 467 mg g-1, respectively.